Best Customer Selection Decision Support System With Elimination And Choise Translation Reality (Electre) Method - Martinus Giawa; Paska Marto Hasugian (Information Technology and Science (ITScience), 2020)
Currently, many companies still use manual in doing any one of them is an office job CV. Independent cooperative. Based on the results of research on the CV. Koperasi Mandiri to determine the best customer still does not have a conventional and special methods and are less effective. Based on the results of this research make customer Election Decision Support System Best with ELECTRE method. Where the method ELECTRE perform testing based on criteria sort by value and ranking obtained using pairwise comparison of alternatives based on any appropriate criteria.